2004
DOI: 10.1186/1477-3163-3-2
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: BackgroundEpidemiological studies have linked the consumption of chlorinated surface waters to an increased risk of two major causes of human mortality, colorectal and bladder cancer. Trihalomethanes (THMs) are by-products formed when chlorine is used to disinfect drinking water. The purpose of this study was to examine the ability of the THMs, trichloromethane (TCM), bromodichloromethane (BDCM), dibromochloromethane (DBCM), and tribromomethane (TBM), to induce DNA strand breaks (SB) in (1) CCRF-CEM human lymp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(1 citation statement)
references
References 29 publications
(30 reference statements)
0
1
0
Order By: Relevance
“…Research to date has focused on the four regulated THMs: chloroform, bromoform, bromodichloromethane (BDCM), and dibromochloromethane (DBCM) ( Da Silva et al 2000 ). Toxicologic studies have shown THMs may result in adverse effects in laboratory animals, including hepatotoxicity, nephrotoxicity, mutagenesis, carcinogenicity, and adverse reproductive effects ( DeAngelo et al 2002 ; Geter et al 2004 ; International Life Science Institute 1995 ; Keegan et al 1998 ; Landi et al 1999 ; Agency for Toxic Substances and Disease Registry 1993 ).…”
mentioning
confidence: 99%
“…Research to date has focused on the four regulated THMs: chloroform, bromoform, bromodichloromethane (BDCM), and dibromochloromethane (DBCM) ( Da Silva et al 2000 ). Toxicologic studies have shown THMs may result in adverse effects in laboratory animals, including hepatotoxicity, nephrotoxicity, mutagenesis, carcinogenicity, and adverse reproductive effects ( DeAngelo et al 2002 ; Geter et al 2004 ; International Life Science Institute 1995 ; Keegan et al 1998 ; Landi et al 1999 ; Agency for Toxic Substances and Disease Registry 1993 ).…”
mentioning
confidence: 99%